A pre-coated water-based epoxy thread locking conductive adhesive

By applying water-based epoxy thread locking conductive adhesive on the screws, and using modified scale graphite, carbon nanotubes and graphene to build a conductive network, the problems of insufficient conductivity and poor curing stability of existing adhesives are solved, and the micro-based The efficient bonding and conductive properties in electronic products are suitable for the application needs of the electronics industry.

CN118909578BActive Publication Date: 2024-12-20CHINA LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411397868.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-20
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

In the fixing of screws of existing adhesives, there are problems such as insufficient conductivity, poor curing stability, poor vibration resistance and inconsistent environmental protection requirements in microelectronics products, which are difficult to meet the application needs of the electronics industry.

Method used

Develop a pre-coated water-based epoxy thread-locked conductive adhesive containing conductive carbon, conductive metal powder, coated epoxy microcapsules and adhesive emulsion, through modified scale graphite, modified carbon nanotubes and modified graphene Build a dense conductive network, combine with epoxy resin for chemical curing to form a dense conductive network.

Benefits of technology

It realizes conductivity, bonding strength and stability in fasteners, complies with strict regulations in the electronics industry, has excellent conductivity and long-term storage stability, and is suitable for thin-filled electronic products applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of adhesives, and discloses a pre-coating water-based epoxy thread locking conductive adhesive. The composition of the pre-coating water-based epoxy thread locking conductive adhesive includes, by mass percentage, 0-20% conductive carbon, 0-60% conductive metal powder, 5-40% coated epoxy microcapsules, 0.5-15% epoxy curing agent, 5-35% bonding emulsion, 0-3% functional additives, and the rest is deionized water. The preparation method thereof comprises the following steps: adding conductive carbon or conductive metal powder and functional additives to deionized water, stirring evenly, and setting aside; adding coated epoxy microcapsules, epoxy curing agent, bonding emulsion, and functional additives to deionized water, stirring evenly, and setting aside; mixing the substances prepared in step S1 and step S2 evenly to obtain a pre-coating water-based epoxy thread locking conductive adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a pre-coated water-based epoxy thread locking conductive adhesive. Background Art

[0002] The fixing of various parts of microelectronic products such as mobile phones, watches, and headphones requires screws of M1.6 and below. In order to meet the requirements of anti-vibration, anti-falling and long-term anti-loosening, a layer of polymer material needs to be coated on the screws. There are three main types of pre-coated thread lockers on the market: a. Powdered nylon, which is a physical glue that requires high temperature melting, and has insufficient unscrewing torque and vibration resistance; b. Acrylic anaerobic glue. Although this chemical glue has high strength, due to the tolerance of the screws and nuts themselves, and the screws used in the electronics industry are generally smaller than M1.6, the bite length and fit clearance cannot effectively meet the " "Anaerobic" is needed, so the curing stability of this type of adhesive is insufficient and cannot be used on a large scale in the electronics industry; c. Epoxy microcapsule pre-coated thread glue. This type of adhesive has obvious advantages in curing strength, stability, corrosion resistance, vibration resistance, and fall resistance. It is a type of pre-coated thread glue that leading consumer electronics companies favor very much. Patents CN111518500A and CN104893635A describe solvent-based one-component epoxy thread locking adhesives, but they do not meet environmental protection requirements and have an adverse effect on the conductivity of screws, which does not meet the application requirements of specific scenarios. Therefore, the development of conductive adhesives for use on screws has very obvious practical value. Summary of the invention

[0003] The object of the present invention is to provide a pre-coated water-based epoxy thread locking conductive adhesive to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A pre-coating water-based epoxy thread locking conductive adhesive comprises, by mass percentage, 0-20% of conductive carbon, 0-60% of conductive metal powder, 2-40% of coated epoxy microcapsules, 0.5-15% of epoxy curing agent, 5-35% of bonding emulsion, 0-33% of functional additives, and the remainder is deionized water.

[0006] Furthermore, the conductive carbon includes any one or more of conductive carbon black, conductive graphene, conductive carbon nanotubes, and conductive carbon fibers.

[0007] Furthermore, the conductive metal powder includes any one of silver powder, nickel powder, copper powder, and silver-coated copper powder.

[0008] Furthermore, the preparation method of the coated epoxy microcapsules comprises the following steps:

[0009] Add melamine and urea to the formaldehyde solution, stir evenly, add triethylamine to adjust the pH to 8.8-9.2, heat to 70-75°C and stir for 1-1.5h, cool to room temperature for use, and obtain solution A; heat epoxy resin, epoxy resin diluent, and sodium dodecyl sulfate to 60-65°C and stir evenly, add deionized water and keep warm and stir to obtain emulsion A; slowly and uniformly add solution A to emulsion A, add hydrochloric acid to adjust the pH to 2.4-2.6, heat to 70-75°C and react for 3-3.5h, filter, wash, and dry to obtain coated epoxy microcapsules;

[0010] Furthermore, the slow and uniform dripping time is 55-65min;

[0011] Furthermore, the molar ratio of melamine:urea:formaldehyde solution is (0.05-0.1):(1-2):(2-4);

[0012] Furthermore, the mass ratio of the epoxy resin:epoxy resin diluent is 10:(0.5-5), and the amount of sodium dodecyl sulfate added is 0.2% of the total mass of the epoxy resin and the epoxy resin diluent;

[0013] Further, the mass ratio of solution A:emulsion A is 10:(5-15);

[0014] Furthermore, the functional additives include dispersants, coupling agents, emulsifiers, defoamers, adhesive additives, and curing accelerators.

[0015] Furthermore, the epoxy curing agent includes 1,3-bis(aminomethyl)cyclohexane, trimethylhexanediamine, and NX-8101.

[0016] Furthermore, the bonding emulsion includes VINNAPAS® EP708 emulsion and Uniplex® 5132 emulsion.

[0017] Furthermore, the dispersant includes LUCRAMUL DA345 and BYK333.

[0018] Furthermore, the coupling agent includes KH560.

[0019] Furthermore, the emulsifier includes trimethylhexanediamine and sodium dodecyl sulfate.

[0020] Furthermore, the defoaming agent includes SILFOAM® SD 670.

[0021] Furthermore, the bonding aid includes HDK® N20.

[0022] Furthermore, the curing accelerator includes DMP-30.

[0023] Furthermore, the epoxy resin includes E51.

[0024] Furthermore, the epoxy diluent includes n-butyl glycidyl ether.

[0025] Furthermore, the conductive carbon includes composite conductive carbon composed of modified flake graphite, modified carbon nanotubes and modified graphene.

[0026] Furthermore, the mass ratio of modified flake graphite: modified carbon nanotube: modified graphene in the composite conductor is (1-3): (1-3): (1-3).

[0027] Furthermore, the preparation method of the modified flake graphite comprises the following steps:

[0028] The flake graphite is placed in deionized water, ultrasonically dispersed for 1-2 hours, ferrous sulfate is added, heated to 85-90° C., 30% v / v hydrogen peroxide solution is added, reacted for 12-14 hours, washed, and dried to obtain modified flake graphite.

[0029] Furthermore, the mass ratio of the flake graphite to ferrous sulfate is (1-3):(5-15).

[0030] Furthermore, the method for preparing the modified carbon nanotubes comprises the following steps:

[0031] KH550 was added to 95% v / v ethanol, heated to 60-65°C and stirred for reaction for 3-3.5 hours, hydroxylated multi-walled carbon nanotubes were added, the mixture was stirred for reaction for 3-3.5 hours, suction filtered, washed, and dried to obtain silane coupling agent modified carbon nanotubes; silane coupling agent modified carbon nanotubes were added to deionized water, stirred evenly, anhydrous ethanol was added, ultrasonically dispersed for 1-1.5 hours, dopamine hydrochloride and Tris-HCl were added, the pH of the reaction system was adjusted to 8.4-8.6, heated to 80-85°C and stirred for reaction for 6-8 hours, suction filtered, washed, and dried to obtain modified carbon nanotubes.

[0032] Furthermore, the amount of KH550 added is 2-3% of the mass of the carboxylated multi-walled carbon nanotubes; the mass ratio of the silane coupling agent modified carbon nanotubes: dopamine hydrochloride: Tris-HCl is (1-2):(0.2-0.4):1.2.

[0033] Furthermore, the method for preparing the modified graphene comprises the following steps:

[0034] The pH value of 95% v / v ethanol was adjusted to 3-4, KH560 was added and ultrasonically stirred for 1-2 hours, graphene oxide was added, the mixture was heated to 70-75°C and stirred for reaction for 4-5 hours, suction filtered, washed, dried, and ground to obtain modified graphene oxide; the modified graphene oxide was ultrasonically dispersed in anhydrous ethanol, hydrazine hydrate was added, the mixture was heated to 60-65°C and stirred for reaction for 12-14 hours, filtered, washed, dried, and ground to obtain modified graphene.

[0035] Furthermore, the mass ratio of the graphene oxide:KH560 is (0.4-1):(1.2-3); the mass ratio of the modified graphene oxide:hydrazine hydrate is 1:(10-12).

[0036] A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive comprises the following steps:

[0037] S1: Add any one or two of the conductive carbon and conductive metal powder and functional additive A into deionized water, stir evenly, and set aside; the functional additive A includes a dispersant and a coupling agent;

[0038] S2: Add the coated epoxy microcapsules, epoxy curing agent, bonding emulsion and functional additive B into deionized water, stir evenly and set aside; the functional additive B includes an emulsifier, a defoaming agent, a bonding additive and a curing accelerator.

[0039] S3: Evenly mix the materials prepared in step S1 and step S2 to obtain a pre-coated water-based epoxy thread locking conductive adhesive.

[0040] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0041] ① The conductive adhesive of the present invention can be used in fasteners. It is a chemical reaction curing adhesive that takes into account conductivity, pre-coating properties, and bonding strength requirements. It is the first time it has appeared in the industry.

[0042] ② The adhesive of the present invention is water-based, odorless, safe and environmentally friendly, and complies with the most stringent regulations in the electronics industry.

[0043] ③ The conductive adhesive of the present invention disperses the conductive carbon or conductive metal powder in advance (to prevent the conductive powder from agglomerating), and then mixes it with the epoxy resin component that has a chemical curing effect to ensure dispersion and storage stability, stable conductive performance, and an effective storage period of >1 year.

[0044] ④ The conductive adhesive of the present invention has a pre-coating function and meets the screw strength and vibration requirements of the electronics industry, and is very suitable for the application of thin-film electronic products.

[0045] ⑤ On the basis of conductive carbon, the present invention further innovatively selects a ternary carbon-based filler strategy, that is, selects flake graphite modified by segmented reaction as the conductive skeleton, and uses KH550, dopamine dual-modified multi-walled carbon nanotubes, and KH560 modified graphene as fillers to fill the flake graphite conductive skeleton. At the same time, the Π-Π stacking effect between dopamine and graphene is utilized, and the modified multi-walled carbon nanotubes with a stick-like structure are used as longitudinal extension and bonding bridges to construct an overlapping and tightly bonded conductive network between flake graphite and graphene, which makes up for the poor conductivity between traditional graphite sheets. Using modified multi-walled carbon nanotubes as "adhesives", modified flake graphite, modified carbon nanotubes and modified graphene are closely connected. Then, through the self-sedimentation characteristics of large-size flake graphite, they are densely stacked into a layered structure at the bottom of the epoxy resin. Finally, through the epoxy group of KH560 modified graphene (epoxy treatment of modified graphene oxide is to avoid the occurrence of poor stacking dispersion of graphene oxide during the curing process), it is closely connected with the epoxy resin during the curing process. Accompanied by continuous reactions of stacking and cross-linking, it is finally cured to obtain a conductive adhesive with a dense conductive network, which has excellent conductive properties. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] In the following examples, the dendritic silver-coated copper conductive powder model is YL-B1004, purchased from Guangzhou Yinfeng Metal Technology Co., Ltd.; the chain bead-shaped silver-coated copper powder is purchased from Ningbo Jinlei Nanomaterial Technology Co., Ltd.; the silver nanowire model is JL-Ag-X20 purchased from Ningbo Jinlei Nanomaterial Technology Co., Ltd.; NX-8101 is purchased from Cardolite Chemical (Zhuhai) Co., Ltd.; graphene oxide is purchased from Changzhou Sixth Element Materials Technology Co., Ltd.; hydroxyl multi-walled carbon nanotubes, XFDP04 graphene aqueous slurry (4% solid content), and flake graphite with a specification of 500 mesh are all purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; the remaining raw materials are commercially available.

[0048] The preparation method of coated epoxy resin comprises the following steps:

[0049] Melamine, urea and formaldehyde solution were mixed in a molar ratio of 0.05:1:2, triethylamine was added to adjust the pH to 9, heated to 70°C and stirred for 1 hour, cooled to room temperature for use, and solution A was obtained;

[0050] Epoxy resin E51 and n-butyl glycidyl ether were added into a reaction container at a mass ratio of 10:0.5, 0.2 wt % sodium dodecyl sulfate was added, heated to 60° C. and stirred evenly, and deionized water was added and stirred while maintaining the temperature to obtain emulsion A;

[0051] Solution A was slowly and uniformly added to emulsion A, hydrochloric acid was added to adjust the pH to 2.5, heated to 70°C for reaction for 3 hours, filtered, washed, and dried to obtain coated epoxy microcapsules. The mass ratio of solution A to emulsion A was 10:5.

[0052] Example 1: A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive: S1: Add 41wt% of graphene water-based slurry XFDP04, 3.4wt% of thin-layer graphene nanosheets XFQ022, and 0.4wt% of dispersant LUCRAMUL DA345 into deionized water, stir evenly, and set aside;

[0053] S2: Add 9.3wt% of coated epoxy microcapsules, 0.2wt% of curing agent accelerator DMP-30, 4.5% of 1,3-bis(aminomethyl)cyclohexane, 16.5wt% of VINNAPAS®EP708 emulsion, and 0.2wt% of SILFOAM®SD 670 into deionized water, stir evenly, and set aside;

[0054] S3: Evenly mix the materials prepared in step S1 and step S2 to obtain a pre-coated water-based epoxy thread locking conductive adhesive.

[0055] Example 2: A method for preparing a pre-coating water-based epoxy thread locking conductive adhesive: S1: Add 18wt% of graphene water-based slurry XFDP04, 30wt% of dendritic silver-coated copper conductive powder YL-B1004, and 0.2wt% of dispersant BYK333 into deionized water, stir evenly, and set aside;

[0056] S2: Add 4wt% of coated epoxy microcapsules, 0.1wt% of curing agent accelerator DMP-30, 1% 1,3-bis(aminomethyl)cyclohexane, 9.6wt% of VINNAPAS®EP708 emulsion, and 0.1wt% of SILFOAM®SD 670 into deionized water, stir evenly, and set aside;

[0057] S3: Evenly mix the materials prepared in step S1 and step S2 to obtain a pre-coated water-based epoxy thread locking conductive adhesive.

[0058] Example 3: A method for preparing a pre-coating water-based epoxy thread locking conductive adhesive: S1: Add 42wt% chain bead-shaped silver-coated copper, 10wt% silver nanowire JL-Ag-X20, and 0.5wt% coupling agent KH560 into deionized water, stir evenly, and set aside;

[0059] S2: Add 3.5wt% of coated epoxy microcapsules, 0.08wt% of curing agent accelerator DMP-30, 0.85wt% of trimethylhexanediamine, and 15wt% of Uniplex® 5132 emulsion into deionized water, stir evenly, and set aside;

[0060] S3: Evenly mix the materials prepared in step S1 and step S2 to obtain a pre-coated water-based epoxy thread locking conductive adhesive.

[0061] Example 4: A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive: S1: Place 1 g of flake graphite in deionized water, ultrasonically disperse for 1 h, add 5 g of ferrous sulfate, heat to 85°C, add 30% v / v hydrogen peroxide solution, react for 12 h, wash, and dry to obtain modified flake graphite;

[0062] S2: Add 0.2g KH550 to 95% v / v ethanol, heat to 60°C and stir for 3h, add 10g hydroxylated multi-walled carbon nanotubes, keep warm and stir for 3h, filter, wash, and dry to obtain silane coupling agent modified carbon nanotubes; add 1g silane coupling agent modified carbon nanotubes to deionized water, stir evenly, add anhydrous ethanol, ultrasonically disperse for 1h, add 0.2g dopamine hydrochloride and 1.2g Tris-HCl, adjust the pH of the reaction system to 8.5, heat to 80°C and stir for 6h, filter, wash, and dry to obtain modified carbon nanotubes;

[0063] S3: Adjust the pH of 95% v / v ethanol to 3, add 1.2 g KH560 and stir ultrasonically for 1 h, add 0.4 g graphene oxide, heat to 70 ° C and stir for 4 h, filter, wash, dry, grind to obtain modified graphene oxide; ultrasonically disperse 1 g of modified graphene oxide in anhydrous ethanol, add 10 g of hydrazine hydrate, heat to 60 ° C and stir for 12 h, filter, wash, dry, grind to obtain modified graphene;

[0064] S4: preparing composite conductive carbon by mixing modified flake graphite, modified carbon nanotube and modified graphene in a mass ratio of 2:1:1;

[0065] S5: Add 10.2wt% composite conductive carbon and 0.5wt% coupling agent KH560 into deionized water and stir evenly for later use;

[0066] S6: Add 12.2wt% of coated epoxy microcapsules, 0.32wt% of curing agent accelerator DMP-30, 3.5wt% of trimethylhexanediamine, and 20wt% of Uniplex® 5132 emulsion into deionized water, stir evenly, and set aside;

[0067] S7: Evenly mix the materials prepared in step S5 and step S6 to obtain a pre-coated water-based epoxy thread locking conductive adhesive.

[0068] Example 5: A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive: S1: Place 1 g of flake graphite in deionized water, ultrasonically disperse for 1 h, add 5 g of ferrous sulfate, heat to 85°C, add 30% v / v hydrogen peroxide solution, react for 12 h, wash, and dry to obtain modified flake graphite;

[0069] S2: Add 0.2g KH550 to 95% v / v ethanol, heat to 60°C and stir for 3h, add 10g hydroxylated multi-walled carbon nanotubes, keep warm and stir for 3h, filter, wash, and dry to obtain silane coupling agent modified carbon nanotubes; add 1g silane coupling agent modified carbon nanotubes to deionized water, stir evenly, add anhydrous ethanol, ultrasonically disperse for 1h, add 0.2g dopamine hydrochloride and 1.2g Tris-HCl, adjust the pH of the reaction system to 8.5, heat to 80°C and stir for 6h, filter, wash, and dry to obtain modified carbon nanotubes;

[0070] S3: Adjust the pH of 95% v / v ethanol to 3, add 1.2 g KH560 and stir ultrasonically for 1 h, add 0.4 g graphene oxide, heat to 70 ° C and stir for 4 h, filter, wash, dry, grind to obtain modified graphene oxide; ultrasonically disperse 1 g of modified graphene oxide in anhydrous ethanol, add 10 g of hydrazine hydrate, heat to 60 ° C and stir for 12 h, filter, wash, dry, grind to obtain modified graphene;

[0071] S4: preparing composite conductive carbon by mixing modified flake graphite, modified carbon nanotube and modified graphene in a mass ratio of 3:3:3;

[0072] S5: Add 10.6wt% composite conductive carbon and 0.5wt% coupling agent KH560 into deionized water, stir evenly, and set aside;

[0073] S6: Add 12.5wt% of coated epoxy microcapsules, 0.32wt% of curing agent accelerator DMP-30, 3.5wt% of trimethylhexanediamine, and 20wt% of Uniplex® 5132 emulsion into deionized water, stir evenly, and set aside;

[0074] S7: Evenly mix the materials prepared in step S5 and step S6 to obtain a pre-coated water-based epoxy thread locking conductive adhesive.

[0075] Comparative Example 1: A method for preparing a pre-coating water-based epoxy thread locking conductive adhesive: 15wt% of coated epoxy microcapsules, 0.2wt% of curing accelerator DMP-30, 6.7wt% of trimethylhexanediamine, 30wt% of Uniplex® 5132 emulsion, 0.5wt% of KH560, and 1wt% of HDK® N20 are added to deionized water, and mixed evenly under low-speed stirring to obtain a pre-coating water-based epoxy thread locking conductive adhesive.

[0076] Comparative Example 2: A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive: S1: Add 36wt% of dendritic silver-coated copper conductive powder YL-B1004 and 0.5wt% of coupling agent KH560 into deionized water, stir evenly, and set aside;

[0077] S2: Add 7wt% of coated epoxy microcapsules, 0.2wt% of curing agent accelerator DMP-30, 0.8wt% of trimethylhexanediamine, 5.3wt% of NX-8101, 10wt% of Uniplex® 5132 emulsion, and 1wt% of HDK® N20 into deionized water, stir evenly, and set aside;

[0078] S3: Evenly mix the materials prepared in step S1 and step S2 to obtain a pre-coated water-based epoxy thread locking conductive adhesive.

[0079] Comparative Example 3: A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive: S1: 1 g of multi-walled carbon nanotubes was placed in deionized water, ultrasonically dispersed for 1 h, 5 g of ferrous sulfate was added, heated to 85°C, 30% v / v hydrogen peroxide solution was added, reacted for 12 h, washed, and dried to obtain modified carbon nanotubes;

[0080] S2: Add 0.2g KH550 to 95% v / v ethanol, heat to 60°C and stir for 3h, add 10g hydroxylated flake graphite, keep warm and stir for 3h, filter, wash, and dry to obtain silane coupling agent modified flake graphite; add 1g silane coupling agent modified flake graphite to deionized water, stir evenly, add anhydrous ethanol, ultrasonically disperse for 1h, add 0.2g dopamine hydrochloride and 1.2g Tris-HCl, adjust the pH of the reaction system to 8.5, heat to 80°C and stir for 6h, filter, wash, and dry to obtain modified flake graphite;

[0081] S3: Adjust the pH of 95% v / v ethanol to 3, add 1.2 g KH560 and stir ultrasonically for 1 h, add 0.4 g graphene oxide, heat to 70 ° C and stir for 4 h, filter, wash, dry, grind to obtain modified graphene oxide; ultrasonically disperse 1 g of modified graphene oxide in anhydrous ethanol, add 10 g of hydrazine hydrate, heat to 60 ° C and stir for 12 h, filter, wash, dry, grind to obtain modified graphene;

[0082] The remaining steps are the same as those in Example 5.

[0083] Comparative Example 4: A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive: S1: 1 g of flake graphite is placed in deionized water, ultrasonically dispersed for 1 h, 5 g of ferrous sulfate is added, heated to 85°C, 30% v / v hydrogen peroxide solution is added, reacted for 12 h, washed, and dried to obtain modified flake graphite;

[0084] S2: Add 0.2 g KH560 to 95% v / v ethanol, heat to 60°C and stir for 3 h, add 10 g hydroxylated multi-walled carbon nanotubes, keep warm and stir for 3 h, filter, wash, and dry to obtain modified carbon nanotubes;

[0085] S3: Adjust the pH of 95% v / v ethanol to 3, add 1.2g KH550 and stir ultrasonically for 1-2h, add 0.4g graphene oxide, heat to 70℃ and stir for 4-5h, filter, wash, dry and grind to obtain modified graphene oxide; ultrasonically disperse 1g modified graphene oxide in anhydrous ethanol, add 10g hydrazine hydrate, heat to 60℃ and stir for 12h, filter, wash, dry and grind to obtain modified reduced graphene; add 1g modified reduced graphene to deionized water, stir evenly, add anhydrous ethanol, ultrasonically disperse for 1h, add 0.2g dopamine hydrochloride and 1.2g Tris-HCl, adjust the pH of the reaction system to 8.5, heat to 80℃ and stir for 6h, filter, wash and dry to obtain modified graphene;

[0086] The remaining steps are the same as those in Example 5.

[0087] Comparative Example 5: A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive: S1: Place 1 g of flake graphite in deionized water, ultrasonically disperse for 1 h, add 5 g of ferrous sulfate, heat to 85°C, add 30% v / v hydrogen peroxide solution, react for 12 h, wash, and dry to obtain modified flake graphite;

[0088] S2: Add 0.2g KH550 to 95% v / v ethanol, heat to 60°C and stir for 3h, add 10g hydroxylated multi-walled carbon nanotubes, keep warm and stir for 3h, filter, wash, and dry to obtain silane coupling agent modified carbon nanotubes; add 1g silane coupling agent modified carbon nanotubes to deionized water, stir evenly, add anhydrous ethanol, ultrasonically disperse for 1h, add 0.2g dopamine hydrochloride and 1.2g Tris-HCl, adjust the pH of the reaction system to 8.5, heat to 80°C and stir for 6h, filter, wash, and dry to obtain modified carbon nanotubes;

[0089] S3: Adjust the pH of 95% v / v ethanol to 3, add 1.2 g KH560 and stir ultrasonically for 1 h, add 0.4 g graphene oxide, heat to 70 ° C and stir for 4 h, filter, wash, dry and grind to obtain modified graphene;

[0090] The remaining steps are the same as those in Example 5.

[0091] Experiment: Resistance test method: Apply conductive glue to the screw as required, screw it into an aluminum plate with the same size as the screw. The aluminum plate has threaded holes with the same spacing. Leave 1-2 threads when the screw is screwed in. Measure the resistance after curing for 48 hours. Place the positive and negative ends of the resistance tester on the screw head and the other end on the aluminum plate, fix the downward pressure, and read the resistance value.

[0092] The test bolt of the present invention has a size of M1.4×0.3×2.37L, an installation torque of 0.3 kgf.cm, and an installation speed of 490 rpm.

[0093] Vibration test reference standard: DIN65151.

[0094] Table 1 Summary of conductive adhesive performance test results

[0095]

[0096] Conclusion: The conductive adhesive prepared by the present invention has favorable conductive properties and physical properties.

[0097] In Comparative Example 1, the conductive adhesive was prepared by a traditional blending method, and the conductive performance was poor.

[0098] In Comparative Example 2, a single pure metal powder is used as the conductive filler to prepare the conductive adhesive, resulting in a larger resistance value and reduced conductive performance.

[0099] In Comparative Example 3, the modification method of the original modified flake graphite is swapped with the modified carbon nanotubes, resulting in the modified carbon nanotubes being unable to serve as a bridge for bonding flake graphite and graphene, and being stacked on the surface of flake graphite, resulting in reduced conductivity.

[0100] In Comparative Example 4, the rigidity of the original modified graphene is swapped with the modified carbon nanotubes, resulting in the inability to further fill the flake graphite. Similar to Comparative Example 3, the graphite is mostly concentrated on the surface, and the conductive performance is reduced.

[0101] In Comparative Example 5, the modified graphene was not further reduced using hydrazine hydrate, resulting in reduced graphene dispersion and conductivity.

[0102] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A pre-coated water-based epoxy thread locking conductive adhesive, characterized in that: The composition of the pre-coated water-based epoxy thread locking conductive adhesive includes, by mass percentage, 0-20% conductive carbon, 0-60% conductive metal powder, 2-40% coated epoxy microcapsules, 0.5-15% epoxy curing agent, 5-35% adhesive emulsion, 0-3% functional additive, and the rest is deionized water; the added amounts of the conductive carbon and the conductive metal powder are not zero; The conductive carbon comprises a composite conductive carbon composed of modified flake graphite, modified carbon nanotubes and modified graphene; the mass ratio of modified flake graphite: modified carbon nanotubes: modified graphene in the composite conductive carbon is (1-3): (1-3): (1-3); The preparation method of the modified flake graphite comprises the following steps: The flake graphite is placed in deionized water, ultrasonically dispersed for 1-2 hours, ferrous sulfate is added, heated to 85-90° C., a 30% v / v hydrogen peroxide solution is added, reacted for 12-14 hours, washed, and dried to obtain modified flake graphite; the mass ratio of the flake graphite to ferrous sulfate is (1-3):(5-15); The method for preparing the modified carbon nanotubes comprises the following steps: Add KH550 to 95% v / v ethanol, heat to 60-65°C and stir to react for 3-3.5h, add hydroxylated multi-walled carbon nanotubes, keep warm and stir to react for 3-3.5h, filter, wash, and dry to obtain silane coupling agent modified carbon nanotubes; add silane coupling agent modified carbon nanotubes to deionized water, stir evenly, add anhydrous ethanol, ultrasonically disperse for 1-1.5h, add dopamine hydrochloride and Tris-HCl, adjust the pH of the reaction system to 8.4-8.6, heat to 80-85°C and stir to react for 6-8h, filter, wash, and dry to obtain modified carbon nanotubes; the amount of KH550 added is 2-3% of the mass of the carboxylated multi-walled carbon nanotubes; the mass ratio of the silane coupling agent modified carbon nanotubes: dopamine hydrochloride: Tris-HCl is (1-2):(0.2-0.4):1.2; The preparation method of the modified graphene comprises the following steps: The pH value of 95% v / v ethanol is adjusted to 3-4, KH560 is added and ultrasonically stirred for 1-2 hours, graphene oxide is added, heated to 70-75° C. and stirred for reaction for 4-5 hours, filtered, washed, dried, and ground to obtain modified graphene oxide; the modified graphene oxide is ultrasonically dispersed in anhydrous ethanol, hydrazine hydrate is added, heated to 60-65° C. and stirred for reaction for 12-14 hours, filtered, washed, dried, and ground to obtain modified graphene; the mass ratio of the graphene oxide:KH560 is (0.4-1):(1.2-3); the mass ratio of the modified graphene oxide:hydrazine hydrate is 1:(10-12).

2. The pre-coated water-based epoxy thread locking conductive adhesive according to claim 1, characterized in that: The conductive carbon includes any one or more of conductive carbon black, conductive graphene, conductive carbon nanotubes, and conductive carbon fibers.

3. The pre-coated water-based epoxy thread locking conductive adhesive according to claim 1, characterized in that: The conductive metal powder includes any one of silver powder, nickel powder, copper powder and silver-coated copper powder.

4. The pre-coated water-based epoxy thread locking conductive adhesive according to claim 1, characterized in that: The method for preparing the coated epoxy microcapsules comprises the following steps: Add melamine and urea to the formaldehyde solution, stir evenly, add triethylamine to adjust the pH to 8.8-9.2, heat to 70-75℃ and stir for 1-1.5h, cool to room temperature for use, and obtain solution A; heat epoxy resin, epoxy resin diluent, and sodium dodecyl sulfate to 60-65℃ and stir evenly, add deionized water and keep warm and stir to obtain emulsion A; uniformly add solution A dropwise to emulsion A, and add hydrochloric acid to adjust the pH to 2.4-2.

6. Heat to 70-75° C. and react for 3-3.5 hours, filter, wash, and dry to obtain coated epoxy microcapsules; in the solution A, the molar ratio of melamine: urea: formaldehyde solution is (0.05-0.1): (1-2): (2-4); in the emulsion A, the mass ratio of epoxy resin: epoxy resin diluent is 10: (0.5-5); in the coated epoxy microcapsules, the mass ratio of solution A: emulsion A is 10: (5-15).

5. The pre-coated water-based epoxy thread locking conductive adhesive according to claim 1, characterized in that: The functional additives include dispersants, coupling agents, emulsifiers, defoamers, adhesive additives, and curing accelerators.

6. A method for preparing a pre-coated water-based epoxy thread locking conductive adhesive, characterized in that: The method for preparing the pre-coating water-based epoxy thread locking conductive adhesive according to any one of claims 1 to 5 comprises the following steps: S1: Add any one or two of the conductive carbon and conductive metal powder and functional additive A into deionized water, stir evenly, and set aside; the functional additive A includes a dispersant and a coupling agent; S2: adding the coated epoxy microcapsules, epoxy curing agent, bonding emulsion, and functional additive B into deionized water, stirring evenly, and setting aside; the functional additive B includes an emulsifier, a defoaming agent, a bonding additive, and a curing accelerator; S3: Evenly mix the materials prepared in step S1 and step S2 to obtain a pre-coated water-based epoxy thread locking conductive adhesive.